Learning by doing—teaching systematic review methods in 8 weeks. (14th February 2014) - Li, Tianjing; Saldanha, Ian J.; Vedula, S. Swaroop; Yu, Tsung; Rosman, Lori; Twose, Claire; N. Goodman, Steven; Dickersin, Kay
<x xml:space="preserve">Abstract</x> Objective The objective of this paper is to describe the course "Systematic Reviews and Meta‐analysis" at the Johns Hopkins Bloomberg School of Public Health. Methods A distinct feature of our course is a group project in which students, assigned to multi‐disciplinary groups, conduct a systematic review. In‐class sessions comprise didactic lectures, hands‐on exercises, demonstrations, discussion, and group work. Students also work outside of class to complete the systematic review. Students evaluated the course at the end of the term. We also surveyed students from 2004 to 2012 to learn more about the long‐term impact of the course. Results The course has been offered to more than 800 students since 1995. In our view, aspects that worked well include the hands‐on approach, students working in a multidisciplinary group, intensive interaction with the teaching team, moving to an online approach, and continuous updates of the course content. A persistent issue is the constraint of time. 193 of 211 (91%) survey participants reported that the course is currently useful or as having an impact on their work. Conclusions Our experiences have led us to remain committed to a hands‐on approach. Our course serves as a bridge between classroom learning and real‐world practice, and provides an example of teaching systematic review. Copyright © 2014 John Wiley & Sons, Ltd.